Colombia’s conflict historic commission: the creation of narratives for the conflict and its impact in civil-military relations - Torrijos R, Vicente (2016)
By recognizing the relevance of Historical Commissions in the design of civil- military bonds in post-conflict scenarios, this document identifies the different positions that the Historical for the Conflict in Colombia´s report has developed about the role of the military forces in the conflict. Likewise the document puts itsefforts to evidence its consequences and narratives and to enemphasize the possibilities and concerns that may arise from lectures of the conflict that wrongfully condemn the military forces and affect their legitimacy and symbolic capital.